Pengembangan E-Modul Berbantuan Flipbook Maker untuk Membangun Kemampuan Pemahaman Konsep Siswa di SMK Negeri 4 Padangsidimpuan - Ardiana, Nunik; Elindra, Rahmatika; Siagian, Elida Khairani Annur (JURNAL MathEdu (Mathematic Education Journal), 2025)
Abstract This study aimed to know the Validity, Effectiveness and Practicality of the development of E-Modules assisted by Flipbook Makers in building students’ mathematical concept understanding abilities at SMK Negeri 4 Padangsidimpuan by using the R&D method. The research used the ADDIE design which has 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects involved in this study were 17 students at the tenth grade students of DKV 1 at SMK Negeri 4 Padangsidimpuan. The results of this study indicated the validity of the development of E-Modules assisted by flipbook makers from the three expert lecturers as validators who assessed the aspects of media, materials, and language. The conclusion obtained from this research and development was the validation result from the three validators of 90.5 (very valid category) while the effectiveness of using the module was obtained from the results of the test analysis of students’ mathematical concept understanding abilities with a classical completeness percentage of 94% and the practicality of the product was obtained from the positive response of students as evidenced by filling out the questionnaire with a percentage of 95% (very valid category). It means that the development of e-modules assisted by flipbook makers was concluded to be valid, effective and practical in building students’ mathematical cconceptual understanding abilities at SMK Negeri 4 Padangsidimpuan.